Estimating Fishing Seasons for Scads in Barru District: An Approach for Efficiency and Effectiveness Fishing Business of Management - Muhammad Ridwan; Ilyas; Andi Rusdi Walinono (Hasanuddin University, 2022)
With a coastline of about 78 km, the potential for capture fisheries in the waters of Barru Regency is veryprospective, especially for several groups of purse seine fishermen for kite fishing. This study aims to estimatethe pattern of scads fishing season in Barru Waters, and to simply describe an effective fishing managementinstrument. This study used CPUE time series data (catch per unit effort) from the Marine Fisheries Agency ofBarru Regency in 2017-2020 and interviews with several purse seine fishermen in the last year of 2021. Inaddition, simple satellite imageries of sea surface temperature (SST) and chlorophyll-a were also used todescribe environmental conditions during the peak fishing season for the study period June-August 2021. TheCPUE moving average time series analysis was used to calculate the fishing season index (IMP). The resultsshowed that the peak season for scads fishing occurred in the east season around Barru coastal Waters,especially in June. This condition may correspond to warm temperatures, and relatively high chlorophyllconcentrations. Such conditions create potential fishing grounds for scads fishery along the study area. Thisinformation on scads fishing season is very helpful in improving the quality of management of small pelagicfisheries in Barru and surrounding waters particularly, when is the best time to increase the fishing efforts.